Nitrogen mustard inhibits transcription and translation in a cell free system. - Masta, A (1995)
Nitrogen mustard and its derivatives such as cyclophosphamide, chlorambucil and melphalan are widely used anti-cancer agents, despite their non-specific reaction mechanism. In this study, the effect of alkylation by nitrogen mustard of DNA and RNA (coding for a single protein) was investigated using both a translation system and a coupled transcription/translation system. When alkylated DNA was used as the template for coupled transcription and translation, a single translation product corresponding to the 62 kDa luciferase protein was synthesised. Production of the translated product encoded by this template was inhibited by mustard concentrations as low as 10 nM, and 50% inhibition occurred with 30 nM mustard. A primer extension assay employed to verify alkylation sites on the DNA revealed that all guanine residues on the DNA template are susceptible to alkylation by nitrogen mustard. Similarly, when alkylated RNA was used as the template for protein synthesis, the amount of the 62 kDa luciferase protein decreased with increasing mustard concentration and a range of truncated polypeptides was synthesised. Under these conditions 50% inhibition of translation occurred with approximately 300 nM mustard (i.e. approximately 10 times that required for similar inhibition using an alkylated DNA template). Furthermore, a gel mobility shift assay revealed that mustard alkylation of the RNA template results in the formation of a more stable retarded RNA complex. The functional activity of the luciferase protein decreased with alkylation of both the DNA and RNA templates, with a half-life of loss of activity of 1.1 h for DNA exposed to 50 nM mustard, and 0.5 h for RNA exposed to 50 microM mustard. The data presented support the notion that DNA is a critical molecule in the mode of action of mustards.